THE EFFECT OF QUARTED CARD SNAKES AND LADDER THERAPY ON PATIENTS WITH SOCIAL ISOLATION PROBLEMS IN SCHIZOPHRENIA AT THE BINA LARAS SOCIAL REHABILITATION UNIT IN PASURUAN - Shafahana, Faradhifa; Arfianto, Muhammad Ari (Nurse and Health: Jurnal Keperawatan, 2025)
Background: Social isolation is a common nursing problem experienced by patients with schizophrenia, characterized by decreased ability to interact, withdrawal, and minimal communication with others. Effective nursing therapy is needed to improve patients' social skills, one example of which is group activity therapy using the Snakes and Ladders Quartered Card Game. Purpose: To determine the effect of providing Quarted Card Snakes and Ladders therapy on the socialization skills of Mr. Y with social isolation nursing problems at the Bina Laras Pasuruan Social Rehabilitation Unit. Methods: This research method used a case study approach on one patient with social isolation issues. The intervention, in the form of Quartered Card Snakes and Ladders therapy, was carried out for two days, once per day for approximately 45 minutes. Data were collected through interviews, observation, and documentation. Evaluation of social skills was conducted before and after the intervention using observation sheets in accordance with the Indonesian Nursing Diagnosis Standards (IDHS) and the Indonesian Nursing Outcome Standards (SLHS). Results: Evaluation results showed an improvement in Mr. Y's social skills after therapy. The patient began to make eye contact, introduce himself, participate in games, answer questions, and interact with group members. The patient appeared more confident and active in two-way communication compared to before the intervention. This study was limited by a single-patient case study, a short intervention duration, and the absence of a control group, which restrict the generalizability of the findings. Conclusion: The Snakes and Ladders Quartered Card Therapy has impact social skills in socially isolated patients. This intervention can be used as an alternative to group activity-based psychiatric nursing therapy to enhance social interaction in patients in social rehabilitation facilities.